Induction of apoptosis by cytoplasmically localized wild-type p53 and the S121F mutant super p53 - YASUDA, KATSUHIRO (D.A. Spandidos, 2012)
After DNA damage, p53 is accumulated in the nucleus and transactivates downstream genes and induces apoptosis. There are two pathways in p53-dependent apoptosis, the transactivation-dependent and -independent pathway. In this study, we constructed p53-inducible glioblastoma cell lines and analyzed them for the induction of apoptosis and transactivation of p53-downstream genes after the nuclear or cytoplasmic expression of p53. To sequester p53 in the cytoplasm, we used p53 mutant with arginine to glycine substitution at residue 306 (R306G). Wild-type p53 retained the ability to arrest the cell cycle, and a p53 mutant with serine to phenylalanine substitution at residue 121 (S121F), which has a strong ability to induce apoptosis, retained this ability even when both the wild-type and p53 and S121F mutant were exclusively sequestered from the nucleus into the cytoplasm. Notably, cytoplasmically sequestered wild-type p53 and S121F mutant transactivated the downstream genes with distinct expression profiles, and the strong apoptotic ability of S121F was not associated with its transactivation activity. These results underscore the existence of transactivation-independent apoptosis and cytoplasmic function of p53.